1995
DOI: 10.1007/bf00192369
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cimetidine on pharmacokinetics and pharmacodynamics of losartan, an AT1-selective non-peptide angiotensin II receptor antagonist

Abstract: This was a 2-period randomized, crossover study in 8 healthy males to determine the effects of cimetidine (400 mg q.i.d. for 6 days) on the pharmacokinetics and pharmacodynamic effects of the angiotensin II receptor antagonist, losartan (100 mg). Cimetidine increased the AUC for losartan 18% without affecting the AUC for E-3174, the active metabolite of losartan. The increase in plasma renin activity following losartan was not affected by cimetidine (maximum mean increases 12.6 and 12.1 ng Ang I.ml-1.h-1 witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Biotransformation of losartan to EXP3 174 is catalyzed in human liver microsomes by two cytocrome P450 subfamilies: CYP3A4 and CYP2C9 (52,69). Cimetidine (a histamine H,-antagonist known to inhibit the oxidative metabolism of many drugs) pretreatment resulted in a significant increase in the area under the plasma concentration-time curve (AUC) for losartan but did not alter the AUC for EXP3174 in 8 healthy males (23). This study suggested that cimetidine did not affect the metabolism and excretion of EXP3 174.…”
Section: Pharmacokineticsmentioning
confidence: 73%
See 1 more Smart Citation
“…Biotransformation of losartan to EXP3 174 is catalyzed in human liver microsomes by two cytocrome P450 subfamilies: CYP3A4 and CYP2C9 (52,69). Cimetidine (a histamine H,-antagonist known to inhibit the oxidative metabolism of many drugs) pretreatment resulted in a significant increase in the area under the plasma concentration-time curve (AUC) for losartan but did not alter the AUC for EXP3174 in 8 healthy males (23). This study suggested that cimetidine did not affect the metabolism and excretion of EXP3 174.…”
Section: Pharmacokineticsmentioning
confidence: 73%
“…PRA and plasma angiotensin I1 levels increased markedly after oral administration of losartan to healthy male volunteers; the long-lasting effect on PRA and plasma angiotensin I1 after oral administration of losartan may have resulted from the retention of plasma levels of EXP3174, as mentioned in the section on effects on the RAS (23,43).…”
Section: Clinical Experiencementioning
confidence: 97%
“…Cimetidine does not cause a significant change in the pharmacokinetics (18% increase in AUC) or pharmacodynamics of losartan. 168 On the other hand, grapefruit juice (an inhibitor of dug metabolism) increases the AUC of losartan (by 14%), and decreases the AUC of EXP3174 (by 19%), 169 while fluconazole, decrease the conversion of losartan to EXP-3174. 124,170 Among the inducers of drug metabolism, phenobarbital 171 has minimal effect on the pharmacokinetics (20% increase in the AUC) of losartan or EXP3174.…”
Section: Interactions Of Angiotensin Receptor Blockers With Other Drugsmentioning
confidence: 99%
“…Hossain and Amran (2000) proposed an in vitro interaction study of diltiazem with ranitidine, which was performed by monitoring absorption spectra, conductometric data, and Ardond's spectrophotometric curves. Other antihypertensive drugs, such as fosinopril, captopril, and losartan, and antibacterial drugs, such as enoxacin, cephradine, and cefixime, also were affected by the presence of H 2 antagonists (Sultana et al, 2007a, b;Goldberg et al, 1995;Arayne et al, 2007Arayne et al, , 2008a. Cimetidine (400 mg twice daily) causes a 23% increase in the plasma levels of d-nebivolol (Drug information online, Drugs.com).…”
Section: Introductionmentioning
confidence: 99%